Mycobacterium tuberculosis-Secreted Tyrosine Phosphatases as Targets Against Tuberculosis: Exploring Natural Sources in Searching for New Drugs - Mascarello, Alessandra; Domeneghini Chiaradia-Delatorre, Louise; Mori, Mattia; Terenzi, Hernán; Botta, Bruno (Current Pharmaceutical Design, 2016)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (Mtb), which primarily affects the respiratory tract. Combinations of drugs are used for therapeutic synergism and to prevent the emergence of drug resistant strains, but even first- or secondchoice drugs present some disadvantages, such as significant side effects and the need for long duration of treatments. Thus, new strategies for TB control and treatment are highly demanded. In this context, protein tyrosine phosphatases (PtpA and PtpB) are secreted by Mtb within the host macrophage and they have been shown to contribute to Mtb pathogenicity. The understanding of the role of these PTPs has led to interesting anti-TB drugs discovery. Here, we review the current knowledge on these two proteins as targets for novel anti-TB therapies, with particular emphasis on their mechanism of action and current advancements in developing small molecule inhibitors from natural sources.
Keywords: tyrosine phosphatases